Grazing intensity and nitrogen fertilization on the height variation of ryegrass (Lolium multiflorum Lam.) in integrated crop–livestock systems - Beltran Barriga, Pablo Antonio (2020)
Introduction. Grazing intensity and nitrogen fertilization in integrated crop-livestock system (ICLS) are factors that influence pasture productivity and, consequently, impact on livestock production. Objective. The objective was to evaluate the effect of grazing intensity and nitrogen fertilization on grazing height of ryegrass (Lolium multiflorum Lam. cv. ‘Winter Star’), in an integrated crop-livestock system (ICLS). Materials and methods. A completely randomized block design was used with a 2 x 2 x 5 factorial arrangement, with 3 replications. The first factor was grazing intensity with 2 levels: high height (HH = 25 cm) and low height (LH = 10 cm). The second factor was nitrogen fertilization with two levels: N (nitrogen) applied to the grass (NP) during the winter and N applied in the grain crop (NG) during the summer, both in doses of 200 kg.ha-1 of N. The third factor was the evaluation period (5 periods). Italian ryegrass was considered. Results. In the HHNP treatment, greater homogeneity of the grass and a higher percentage of heights (between 10 and 25 cm) were observed; however, a lower homogeneity with the treatments LHNG and LHNP in which a greater area was detected with heights lower than the lower critical limit (10 cm). Conclusion. It is concluded that a lower grazing intensity and higher nitrogen fertilization (HHNP) offers a greater height of ryegrass and an adequate weight gain in animals in an ICLS. Keywords: Pasture; integrated systems; nitrogen; continuous grazing.